factores socioeconómicos y condiciones de vida de adultos mayores en la cabecera cantonal chilla, año 2023 - Mejia Bermeo, Evelyn Paulina; Gallon Duval, Mildred Natali (Machala: Universidad Tecnica de Machala, 2024)
The present thesis "Socioeconomic Factors and Living Conditions of Elderly Adults in the Cantonal Head of Chilla, Year 2023" focused on determining how socioeconomic factors influence the living conditions of elderly adults in the mentioned locality. The research was carried out using various data collection techniques, such as interviews, surveys, and review of scientific literature, these instruments allowed obtaining a comprehensive view of the environment in which elderly people live and the main problems they face. To achieve the research objective, a combination of qualitative and quantitative methods was used. In the research conducted with 145 elderly adults residing in the cantonal head of Chilla, it was evidenced that elderly people face multiple problems that negatively affect their living conditions. The most significant problems identified were family disinterest and abandonment, lack of financial support from the State, lack of economic resources, insufficient integration into activities at the municipal gerontological center, and inadequate help from the municipal government. This research highlights the relevance of understanding the complex interactions between socioeconomic factors and the living conditions of elderly adults in the cantonal head of Chilla. Through a comprehensive analysis and the implementation of specific measures aimed at improving the quality of life of this vulnerable population, active participation of the various competent institutions could be promoted to strengthen the well-being of elderly people. A high percentage of respondents indicated abandonment by their families as one of their main concerns. Many elderly adults live alone or do not receive the necessary support from their families, increasing their sense of loneliness and vulnerability. The lack of economic resources was identified as a critical problem, with most of the surveyed elderly adults living on limited incomes, making it difficult for them to meet basic needs such as food, housing, and medical care. This situation is aggravated by the lack of an adequate pension system and the scarcity of opportunities in government support programs. The analyzed socioeconomic factors have a significant impact on the living conditions of elderly adults in the cantonal head of Chilla. The lack of integration into activities at the gerontological center, family abandonment, and insufficient economic resources are interrelated problems that require urgent attention. To improve the living conditions of elderly adults in this locality, it is essential to implement concrete measures that address these problems. Additionally, it is important to improve the dissemination and accessibility of activities at the gerontological center, increasing the visibility of the services offered and facilitating access to the center by providing adequate transportation. Moreover, the designed activities will be relevant and attractive to elderly adults, promoting their active participation. It is established that the strategic plan will promote the integral inclusion of elderly adults in the municipal gerontological center of the canton of Chilla, regulating their participation, use, and operation. Additionally, it details the implementation of activities and services aimed at improving the quality of life of these people, as well as the definition of common areas and their care. The plan will enumerate the competencies of state duties, the shared responsibility of families to foster integration, individual and community development, including awareness programs and activities that favor their active participation in the community.
El presente trabajo de titulación "Factores socioeconómicos y condiciones de vida de adultos mayores en la cabecera cantonal Chilla, año 2023" se enfocó en determinar cómo los factores socioeconómicos influyen en las condiciones de vida de los adultos mayores en la mencionada localidad. La investigación se llevó a cabo utilizando diversas técnicas de recolección de datos, tales como entrevistas, encuestas y revisión de literatura científica, estos instrumentos permitieron obtener una visión integral del entorno en el que viven las personas de la tercera edad y las principales problemáticas que enfrentan. Para alcanzar el objetivo de la investigación, se utilizó una combinación de métodos cualitativos y cuantitativos, en la investigación realizada a 145 adultos mayores residentes en la cabecera cantonal de Chilla, se evidencio que las personas de la tercera edad enfrentan múltiples problemas que afectan negativamente su condición de vida, los problemas más significativos identificados fueron el desinterés y abandono familiar, la escasez de apoyo financiero del Estado, la carencia de recursos económicos, la insuficiente integración en actividades del centro gerontológico municipal y la deficiente ayuda por parte del gobierno municipal. Esta investigación destaca la relevancia de entender las complejas interacciones entre los factores socioeconómicos y las condiciones de vida de los adultos mayores en la cabecera cantonal de Chilla. A través de un análisis exhaustivo y la implementación de medidas específicas dirigidas a mejorar la calidad de vida de esta población vulnerable, se podría promover la participación activa de las diversas instituciones competentes para fortalecer el bienestar de las personas de la tercera edad. Un alto porcentaje de los encuestados señaló el abandono por parte de sus familiares como una de las principales preocupaciones, muchos adultos mayores viven solos o no reciben el apoyo necesario de sus familias, lo que incrementa su sensación de soledad y vulnerabilidad; la carencia de recursos económicos fue identificada como un problema crítico, la mayoría de los adultos mayores encuestados viven con ingresos limitados, lo que dificulta su capacidad para cubrir necesidades básicas como alimentación, vivienda y atención médica. Esta situación se ve agravada por la falta de un sistema de pensiones adecuado y la escasez de oportunidades en programas de apoyo gubernamental. Los factores socioeconómicos analizados tienen un impacto significativo en las condiciones de vida de los adultos mayores en la cabecera cantonal de Chilla. La falta de integración en actividades del centro gerontológico, el abandono familiar y la insuficiencia de recursos económicos son problemas interrelacionados que requieren una atención urgente. Para mejorar las condiciones de vida de los adultos mayores en esta localidad, es esencial implementar medidas concretas que aborden estas problemáticas. Y ayuden a mejorar la difusión y accesibilidad de las actividades del centro gerontológico, a su vez, es crucial aumentar la visibilidad de los servicios ofrecidos y facilitar el acceso al centro mediante la provisión de transporte adecuado. Además, las actividades diseñadas serán relevantes y atractivas para los adultos mayores, promoviendo su participación activa. Se establece que el plan estratégico promoverá la inclusión integral del adulto mayor en el centro gerontológico municipal del cantón Chilla, regulando su participación, uso y funcionamiento, además, se detalla la implementación de actividades y servicios destinados a mejorar la calidad de vida de estas personas, así como la definición de áreas comunes y su cuidado, se enumerará las competencias de los deberes del estado, la corresponsabilidad de la familias para fomentar la integración, el desarrollo individual y comunitario, incluyendo programas de sensibilización y actividades que favorezcan su participación activa en la comunidad.
Keywords: FACTORES SOCIOECONOMICOS; CONDICIONES DE VIDA; ADULTOS MAYORES; CABECERA CANTONAL CHILLA; CENTRO GERONTOLOGICO MUNICIPAL